Success of conservative therapy for chronic subdural hematoma patients: a systematic review - Foppen, M.; Bandral, Harssh Verdan; Slot, Kari-Anne Mariam; Vandertop, W. P.; Verbaan, D. (Frontiers in Neurology, 2023)
Background Conservative therapy for chronic subdural hematoma (cSDH) is an option for patients who express no, or only mild symptoms, thereby preventing surgery in some. Because it is not clear for whom conservative therapy is successful, we aimed to estimate the success rate of conservative therapy and to identify which factors might influence success. Methods We systematically searched MEDLINE and EMBASE databases to identify all available publications reporting outcome of conservative therapy for cSDH patients. Studies containing >10 patients were included. The primary outcome was the success rate of conservative therapy, defined as “no crossover to surgery” during follow-up. In addition, factors possibly associated with success of conservative therapy were explored. Bias assessment was performed with the Newcastle Ottowa Scale and the Cochrane risk-of-bias tool. We calculated pooled incidence and mean estimates, along with their 95% confidence intervals (CIs), using OpenMeta[Analyst] software. Results The search yielded 1,570 articles, of which 11 were included in this study, describing 1,019 conservatively treated patients. The pooled success rate of conservative therapy was 66% (95% CI: 50–82%). One study (n = 98) reported smaller hematoma volume to be associated with success, whilst another study (n = 53) reported low hematoma density and absence of paresis at diagnosis to be associated with success. Conclusion Conservative therapy is reported to be successful in the majority of cSDH patients who have either no, or only mild symptoms. Hematoma volume, low hematoma density and absence of paresis could be factors associated with success. However, further research is warranted in order to establish factors consistently associated with a successful conservative therapy. Other No funding was acquired for this study. The study was not registered nor was a study protocol prepared.